2003
DOI: 10.1002/sia.1635
|View full text |Cite
|
Sign up to set email alerts
|

Determination of amount of substance for nanometre‐thin deposits: consistency between XPS, RBS and XRF quantification

Abstract: Quantification on the nanometre scale is a key task in quality control and for the development of new materials in nanotechnology. In this paper we have studied the consistency in the determination of the amount of substance found by XPS peak shape analysis, Rutherford backscattering spectroscopy (RBS) and x-ray fluorescence spectrometry (XRF). To this end, ZnO was deposited by plasma-enhanced chemical vapour deposition on the three substrates. Four different sets of samples were produced, with the amount of Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…8,9,16 The measured spectra J͑E͒, the primary excitation spectra F͑E͒ ͑excited spectrum before electron transport͒, the indepth concentration profile f͑z͒ ͑where z is the depth below the surface͒, and the inelastic electron scattering cross section K͑T͒ for an energy loss T are linked within electron transport theory, which for the particular case of normal emission reads…”
Section: Experimental and Methodsmentioning
confidence: 99%
“…8,9,16 The measured spectra J͑E͒, the primary excitation spectra F͑E͒ ͑excited spectrum before electron transport͒, the indepth concentration profile f͑z͒ ͑where z is the depth below the surface͒, and the inelastic electron scattering cross section K͑T͒ for an energy loss T are linked within electron transport theory, which for the particular case of normal emission reads…”
Section: Experimental and Methodsmentioning
confidence: 99%
“…Finally, the ZnO-3 sample (i.e., 400°C/60 min, Fig. 1c), used as control thick film, shows a homogeneous granular morphology characterized by fairly welldefined round grains having average dimensions of about 10-15 nm [30]. The morphological results provide confidence about two different ZnO deposition mechanisms, depending on the specific deposition temperature used.…”
Section: Physicochemical Characterization Of Ultrathin Zno-based Filmsmentioning
confidence: 79%
“…Experiments were carried out with the standard Al Ka radiation source (hm = 1486.6 eV) at a base pressure of 2 Â 10 À9 Torr. XPS spectra were collected at a photoelectron take-off angle of 45°, which, according to the effective attenuation length values, respectively, of 0.74 nm, for photoelectron from Zn 2p traveling in ZnO [30], and of 3.13 nm, for Si 2p photoelectrons in an organic layer [31], roughly corresponds to an actual sampling depth in the range from about 1.6 nm (bulk ZnO) up to about 6.4 nm (bulk SiO 2 ). Both survey and narrow region scans were recorded, namely Zn 2p, C 1s, Si 2p, O 1s and N 1s peaks, at pass energy and incremental step size of 150 eV/1 eV for survey and 11.85 eV/0.05 eV for the narrow scans, respectively.…”
Section: Physicochemical Characterization Of the Protein-zno Biointermentioning
confidence: 99%
“…Note that the consistency of the relative thicknesses is very good. The previous analysis made by XPS peak shape analysis 1 showed that the ZnO grows in the form of islands. This will give rise to a shadowing effect which depends on the details of the shape and distribution of the aggregates.…”
Section: Analysis Of the Thin Zno Filmsmentioning
confidence: 99%
“…In a recent study, 1 we compared the three techniques: XPSpeak shape analysis, Rutherford backscattering spectroscopy (RBS) and x-ray fluorescence spectrometry (XRF) for their ability to consistently determine the total amount of Zn atoms in ¾1 nm-10 nm thin ZnO films grown on the three substrates: SiO 2 , Al 2 O 3 and an Al foil with a thin Al 2 O 3 layer. The relative values were found to be consistent to within ¾15-20%.…”
Section: Introductionmentioning
confidence: 99%